2007
DOI: 10.1016/j.cub.2007.01.068
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Protein Phosphatases Are Required for Mitosis in Drosophila

Abstract: We identify cell-cycle roles for 22 of 117 Drosophila PPs. Involvement of several PPs in G(2) suggests multiple points for its regulation. Major mitotic roles are played by PP1 with tyrosine PPs and Myotubularin-related PPs having significant roles in regulating chromosome behavior. Finally, depending upon its regulatory subunits, PP2A regulates spindle bipolarity, kinetochore function, and progression into anaphase. Discovery of several novel cell-cycle PPs identifies a need for further studies of protein dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
141
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(155 citation statements)
references
References 55 publications
9
141
1
Order By: Relevance
“…It has been shown that PP1 participates in the control of transcription by interacting with RNA polymerase II and in a splicing process (49 -52). Moreover, it has been observed in many organisms that the impairment of PP1 activity leads to a mitotic arrest (53)(54)(55)(56)(57). Further studies have shown that PP1 activity should be closely controlled to ensure correct centrosome separation and for the segregation/decondensation of chromosomes (6,58,59).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that PP1 participates in the control of transcription by interacting with RNA polymerase II and in a splicing process (49 -52). Moreover, it has been observed in many organisms that the impairment of PP1 activity leads to a mitotic arrest (53)(54)(55)(56)(57). Further studies have shown that PP1 activity should be closely controlled to ensure correct centrosome separation and for the segregation/decondensation of chromosomes (6,58,59).…”
Section: Discussionmentioning
confidence: 99%
“…73,74 A systematic RNAi screen in Drosophila S2 cells revealed that several phosphatases are required to progress through and exit mitosis. 75 In Xenopus egg extracts PP1, PP2A and calcineurin have been shown to oppose the Cdk1 activity. [76][77][78] The decrease in Cdk1 kinase activity itself in anaphase also allows the dephosphorylation of proteins that were previously phosphorylated by mitotic kinases.…”
Section: Regulation Of Chromosome Segregation In Anaphasementioning
confidence: 99%
“…Genetic screens in fission yeast (Kinoshita et al 1990) and small interfering RNA (siRNA) screens in Drosophila cells (Chen et al 2007) had identified the PP1 and PP2A families of phosphatases as playing important roles in mitosis, particularly in anaphase and mitotic exit. In addition, budding yeast depends on Cdc14 to dephosphorylate Cdk substrates (Ser-Pro and Thr-Pro motifs) to promote mitotic exit (reviewed in D'Amours and Amon 2004), a role that does not appear to be conserved in fission yeast or animal cells reviewed in Mocciaro and Schiebel 2010).…”
Section: Inhibiting Protein Phosphatasesmentioning
confidence: 99%